Comparison of Mini Percutaneous Nephrolithotomy and Standard Percutaneous Nephrolithotomy in the Management of Renal Stones of more than 2CM - Majid Khan Kakakhel, Yassar Hussain Patujo, Amjad Saleem, Sami Ullah, Abdullah, Mohib Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: In patients with kidney stones larger than 2 cm, it is intended to evaluate the effectiveness and safety of small percutaneous nephrolithotomy (mini-PCNL) with conventional percutaneous nephrolithotomy (standard-PCNL). Study Design: Retrospective study Place and Duration: Institute of Kidney Diseases, Hayat Abad Medical Complex, Peshawar, 1st July 2019 - 30th June 2021. Methods: Therewere 170 patients of both genders were presented. All the presented patients had renal stones >2cm were admitted for surgery. Detailed demographics of enrolled cases included age,sex, BMI and comorbidities were recorded after taking informed written consent.Patients were equally divided in two groups. Group I received mini percutaneous nephrolithotomy (mini-PCNL) among 85 patients had renal stone size 2-3cm and 85 patients of group II had renal stone >3cm received standard percutaneous nephrolithotomy (standard-PCNL). Post-operative outcomes among both groups were assessed in terms of Stone-free rate (SFR). SPSS 23.0 was used to analyze all data. Results:Among 170 included cases, 114 (67.1%) patients were males and 56 (32.9%) cases were females. We found that 45 (26.5%) patients had age 20-30 years, 50 (29.4%) patients had age 31-40 years and 75 (44.1%) patients had age >40years. Majority of the patients 130 (76.5%) had BMI <25kg/m2 and 40 (23.5%) had BMI >25kg/m2. Comorbidities were hypertension and diabetes mellitus. We found that operative time of group II was lower 40.7±10.9 minutesas compared to group I 52.4±8.13 minutes while hospitalization, blood transfusion and hemoglobin drops were lower in group I as compared to group II. We found that SFR was higher in group I among 80 (94.1%) cases as compared to group II 78 (91.8%) but difference was insignificant. Most common complications were fever, hematuria and urosepsis but their frequency was higher in group I. Conclusion: Mini-PCNL was an efficient and trustworthy substitute for standard-PCNL in the treatment of renal stones larger than 2 cm (30F). Although there is less blood loss, a lower transfusion rate, and a shorter hospital stay than with standard-PCNL, it nevertheless achieves a similar SFR. The 24F standard-PCNL clearly outperforms the mini-PCNL, but not by much. This method, however, requires more time to complete.